TAKHRIJ HADITS (METODE PENELITIAN SUMBER-SUMBER HADITS UNTUK MEMINIMALISIR PENGUTIPAN HADITS SECARA SEPIHAK) - Muhammad Hafil Birbik (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2020)
This article is aimed to describe about ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œtakhrij HaditsÃƒÂ¢Ã¢â€šÂ¬Ã‚Â, that includes the meaning, advantage and methods. From relevant refrences known that ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œtakhrij HaditsÃƒÂ¢Ã¢â€šÂ¬Ã‚Â is and effort to find ÃƒÂ¢Ã¢â€šÂ¬Ã‚ÂmatanÃƒÂ¢Ã¢â€šÂ¬Ã‚Â and ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œsanadÃƒÂ¢Ã¢â€šÂ¬Ã‚Â of Hadits, compeletely from the original references. It clear that the cuality of Hadits is even known by collector directly through researches. The advantages of takhrij are: (a) collecting variety of sanad of the Hadits (b) collecting variety of matan of the Hadits. TheyÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢re the important materials for the research. To implement takhrij Hadits can be used several methods. (1) takhrij from spelling in matan of Hadits, (2) takhrij from first spelling of the Hadits, (3) takhrij from first collector, (4) takhrij from the topic of Hadits, (5) takhrij from classification of Hadits.